2021
DOI: 10.1021/acsaem.0c02859
|View full text |Cite
|
Sign up to set email alerts
|

N,P-Doped Carbon-Based Freestanding Electrodes Enabled by Cellulose Nanofibers for Superior Asymmetric Supercapacitors

Abstract: The preparation of freestanding electrodes with excellent conductivity and mechanical strength plays a vital role in simplifying the electrode fabrication process and reducing the electrode cost. Herein, a N,P-doped self-supporting carbon electrode is synthesized via a combined templating/activating coassisted carbonization procedure and vacuum filtration process. The glucose precursor was first transformed into N,P-doped carbon nanosheets (NPCNs) with a large specific surface area (2073 m 2 g −1 ) and rich he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 68 publications
(125 reference statements)
3
20
0
Order By: Relevance
“…Furthermore, the electrical conductivity of NPCNF-O and NCNF was measured using the four-probe technique. As-designed NPCNF-O shows the high electrical conductivity of 117 S m −1 , which is comparable or superior to that of NCNF (98 S m −1 ) and previously reported carbonbased materials (such as NPCN -f (113 S m −1 ), 81 SGN-900 (152.9 S m −1 ), 82 CNS-800 (226 S m −1 ), 83 and activated carbon (33 S m −1 )). 83 This implies that good conductivity, developed porous structure, and large specific surface area can significantly promote charge and mass transfer during the electrode reaction.…”
Section: T H I S C O N T E N T Isupporting
confidence: 71%
“…Furthermore, the electrical conductivity of NPCNF-O and NCNF was measured using the four-probe technique. As-designed NPCNF-O shows the high electrical conductivity of 117 S m −1 , which is comparable or superior to that of NCNF (98 S m −1 ) and previously reported carbonbased materials (such as NPCN -f (113 S m −1 ), 81 SGN-900 (152.9 S m −1 ), 82 CNS-800 (226 S m −1 ), 83 and activated carbon (33 S m −1 )). 83 This implies that good conductivity, developed porous structure, and large specific surface area can significantly promote charge and mass transfer during the electrode reaction.…”
Section: T H I S C O N T E N T Isupporting
confidence: 71%
“…The pyrrolic and pyridinic N generally follow the redox process in alkaline electrolyte. 14 It was observed that the CV curves of NPC-X (X = 1, 2, 3, and 4) show a rectangular shape and the area under the CV curves is maximum for NPC-2. As the KOH/C ratio increased from 1 to 2, the area under the CV curve increased to maximum and then decreased a little for NPC-3 and NPC-4.…”
Section: Resultsmentioning
confidence: 95%
“…A slight hump near −0.6 V can be attributed to the redox behavior of material arising from the presence of N atoms in the carbon structure. The pyrrolic and pyridinic N generally follow the redox process in alkaline electrolyte …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This free-standing electrode showed a high capacitance (318 F/g at 1.0 A/g) and maintained 188 F/g at 100 A/g in an alkaline electrolyte. Furthermore, an asymmetric supercapacitor composed of NPCN-f (as the negative electrode) and NPCN/MnO2-f syntheiszed by a self-regulated redox method as the positive electrode exhibited a high energy density (41.5 Wh/kg at 182.0 W/kg power density) and remarkable capacitance retention of 93% after 10,000 cycles in a neutral electrolyte [ 131 ]. Surface area plays an important role in developing conductive CNFs, and with the application of doping materials, their conductivity could be remarkable improved.…”
Section: Applications Of Cns-based Functional Materials In Supercapacitorsmentioning
confidence: 99%